Analisis Nilai Sosial dalam Novel Setelah Dia Pergi Karya Dedy Chandra - Jaya Saputra, Wahyu; Shomary, Sudirman (J-LELC: Journal of Language Education, Linguistics, and Culture, 2021)
This research is entitled "Analysis of Social Values ​​in Novels After He Left by Dedy Chandra. This research is based on the social values ​​that exist in the novel After He left by Dedy Chandra. Research problems (1) What is the social value of social interaction contained in the novel after he left by Dedy Chandra? (2) What is the social value of social conflict contained in Dedy Chandra's Novel After He left? (3) What is the social value of social institutions contained in the novel after he left by Dedy Chandra? (4) What is the social value of social change contained in the Novel After He left by Dedy Chandra? This study aims to describe the social value of social interaction. Social conflicts, social institutions and social change obtained from the novel After Dia Goes by Dedy Chandra. This study uses the theory of UU Hamidy (1993), Zubaedi (2005), Haris Priyatna (2013), Sutarjo Adisusilo (2013), Soerjono Soekanto (2005), K. Bertens (2004), Burhanudin Salam (2002). The results of this study found that the number of social aspects found were 31 data of social interaction, 9 data of social conflict, 5 data of social institutions, and 4 social changes. , and kinship as much as 3 data, while social conflict consists of 2 data of care, 6 data of love and affection, and 3 data of kinship, then 4 data of social institutions, of concern, and 1 data of help, and social change namely 2 data of care, 1 data of love and affection, and 1 data of help. So, it can be concluded that the social and social values ​​that occur are efforts to care, help, kinship, and love.